Determinants of emerging technology commercialization: Empirical evidences from MEMS technology - Wang, C.; Bento, P.; Yin, L. (International Journal of Economic Behavior and Organization, 2017)
Currently most of studies on commercialization of the emerging technology considered the context in developed countries like US, Japan, and EU with few research on developing country like China. To fill this gap, taking 112 Chinese Micro-Electro-Mechanical Systems (MEMS) enterprises as a sample, this thesis empirically investigated the determinants of emerging technology in China. Through multiple regression analysis, the empirical results show that technology property, market conditions, regional innovation network, and enterprise capability are main determinants of MEMS commercialization whereas social environment and policy and regulation do not have significant impact on the performance of MEMS commercialization.